Immunogenicity and Reactogenicity of Francisella tularensis Strain 15/23-1 recA - the Candidate for a New Live Tularemia Vaccine - A. N. Mokrievich; G. M. Titareva; T. I. Kombarova; E. A. Ganina; T. B. Kravchenko; I. V. Bakhteeva; G. M. Vakhrameeva; R. I. Mironova; A. I. Borzilov; O. V. Korobova; V. M. Pavlov; I. A. Dyatlov (Эпидемиология и вакцинопрофилактика, 2015)
F. tularensis strain 15/23-1 recA is different from the vaccine strain F. tularensis line 15 NIIEG by lacking one from the two copies of iglC gene and recA gene has reduced its reactogenicity for experimental animals (BALB/c mice and guinea pigs): transient weight reduction is less expressed, as well as leukopenia and thrombocytopenia during the first week after the immunization, compared to vaccine strain. The concentration of gamma-interferon in mice blood serum after 7 days immunized with strain 15/23-1 recA, was 5 times less than in mice immunized with strain 15 NIIEG. The virulence of the modified strain for mice is less than for the strain 15 NIIEG by more than two orders of magnitude. According to histological studies F. tularensis strain 15/23-1 recA stimulates morphologically a more expressed immune rearrangement in the spleen and lymph nodes as compared to F. tularensis strain 15 NIIEG. The difference of strain 15/23-1 recA from vaccine is that it is not detected in the spleens of experimental animals at 21 days after immunization. The level of specific antibodies in sera of immunized mice and guinea pigs were almost identical in both variants and there was no significant difference in the amount of gamma interferon synthesized by splenocytes of mice under specific induction. Immune mice were protected against subcutaneous challenge with virulent strain of tularemia 503 (subsp. holarctica) and protective immunity formed by the strains was lasting more than 180 days.